Mental health and subjectivity at the work of a municipal guard: a study in psychodynamic of work (Cadernos de Psicologia Social do Trabalho, 2008)
This article resulted from a master's degree research that had as objective to understand the implications of reorganization of a municipal guard from a Brazilian capital on the dynamic health/mental suffering of its workers. The theoretical and methodological recital used was the psychodynamic of work, looking for to identify the defensive strategies developed by the workers to prevent illness. In the development of the research it was possible to evidence that the current period of the institution is a transition time, which intervenes with the organization of work, the subjectivity, and the mental health of its servers. The suffering produced at work is cushioned by the mutual cooperation, the possibility of the use of astuteness intelligence and by the recognition happened of a performance with bigger visibility. In the search of the promotion of the mental health in the work one reveals important to develop the institutional spaces of reflection and quarrel on the current paper of the municipal guard in the society.